(untitled) (Revista Argentina de Musicología, 2020)
Drawing on two sets of regulations on theaters in 19th-century Mexico —the Reglamento Interior y Esterior Del Teatro: Para su Mejor Arreglo y Direccion Economica (1824) and the Reglamento para los teatros de México (1853)—, this article analyzes the construction of this important space of civility in the young nation. As occurred across the recently formed Latin American nations, in Mexico, the elite took control over theatrical spaces in the independent country and, through diverse negotiations with entrepreneurs and the operatic companies, established new rules of civility. These were based on a perceived European standard, on the one hand, and a national sense of pride, on the other. To Latin American elites, opera constituted the spectacle par excellence, one where the social order was performed, both on the theater’s stage and in its seats. Regulating it adequately meant the equivalent of government maintaining the social order. The disciplinary actions on behalf of dominant social groups in the complex public space of theatre were inspired by what Foucault called “technologies of power”, which resulted in many tensions.